CSR perceptions and employee creativity: examining serial mediation effects of meaningfulness and work engagement. Issue 1 (24th October 2018) - Chaudhary, Richa; Akhouri, Anuja
Abstract : Purpose: This study aims to explore how corporate social responsibility (CSR) perceptions foster employee creativity. Specifically, an attempt is made to investigate the intervening role of meaningfulness and work engagement to explain the above linkage. Design/methodology/approach: The study sample consisted of 316 employees from different information technology firms in India. Ordinary least square regression procedures were used to test the study hypotheses with the help of SPSS Process macro. Findings: Employees' perceptions of CSR were found to show both direct and indirect effect on their creativity. Work engagement was found to partially mediate the relationship of perceived CSR and creativity. In addition, results supported the serial mediation model where CSR was found to exercise its influence on creativity via meaningfulness and work engagement in a sequential manner. Practical implications: The findings suggest that being a good corporate citizen can pay employers in terms of enhanced employee engagement and creativity, which can provide competitive advantage to the organizations in this highly competitive business environment. Originality/value: This study contributes to the understanding of micro-foundations of CSR by showing whether and how employees' perceptions of CSR relate to various workplace outcomes. Further, by investigating the complex serial mediation process, it contributes to the extant literature by advancing the understanding of the underlying mechanisms through which CSR influences employee creativity.